Development of distribution-free double exponentially and homogeneously weighted moving average lepage schemes - Chan, Kok Ming (2021)
A control scheme is well-known as the most powerful and significant device in statistical process monitoring (SPM). A control scheme no longer only serves the manufacturing sector; instead, it is now playing a remarkable role in the new stage of smart monitoring. Following the current trend, the development of the distribution-free or nonparametric SPM (NSPM)-type scheme is at an active pace. This is because an NSPM-type scheme has a robust in-control (